The predictive validity of the progress assessment, a clinician administered instrument for use in measurement-based care for substance use disorders. (October 2020) - Van Horn, Deborah H.A.; Goodman, Jessica; Lynch, Kevin G.; Bonn-Miller, Marcel O.; Thomas, Tyrone; Del Re, A.C.; Babson, Kimberly; McKay, James R.
Highlights: We tested a brief clinician-administered progress monitoring tool for continuing care. Items were chosen for breadth of coverage of factors known to affect relapse risk. Scores on 5-item "risk" and "protective" scales predicted urine toxicology outcomes. Abstract: We tested the predictive validity of the Progress Assessment (PA), a brief counselor administered tool for use in measurement-based care for substance use disorders. The PA includes 5 items assessing relapse risk and 5 items assessing factors protective against relapse. Data were drawn from a completed study of continuing care for cocaine dependence (McKay et al., 2013) and includes 12 months of follow-up on158 participants (76% male) who received brief telephone or face-to-face sessions. Each session began with the administration of the PA, followed by cognitive-behavioral counseling tied to the results of the PA and anticipated risky situations. Outcome was assessed via urine toxicology every 3 months. As administered in an effectiveness trial, average PA risk and protective scales within each 3-month segment of the study predicted urine toxicology results at the end of that period, with higher risk scores and lower protective scores predicting greater rates of cocaine positive urine drug screens. PA scores did not predict dropout from continuing care participation. The 10-item PA shows promise as a pragmatic clinical tool for ongoing monitoring during continuing care for substance dependence.